Development of Blue Lake Tourism Objects Using SWOT Analysis in Walasiho Village, Wawo District, North Kolaka Regency - Devi Pratiwi; Muhammad Yusuf; Maddatuang Maddatuang (UNM Geographic Journal, 2020)
This study aims to: (1) Assess what potentials can encourage the development of Blue Lake tourism objects in Wawo District, North Kolaka Regency, (2) Knowing the efforts undertaken for the development of the Blue Lake Tourism Object. This type of research is descriptive. The research was conducted at the Blue Lake Tourism Object in Walasiho Village, Wawo District, NorthKolaka Regency. The data was collected by means of observation, interview and documentation and literature review. The data analysis used SWOT analysis. The results of the research show that: (1) The potential that drives the Blue Lake tourism object, namely, the cool climate, the morphology of the areas located on the hills and coasts, water from mountain springs, various flora and fauna, having Paronama tourist objects with (Beauty, Authenticity, Uniqueness), Accessibility which is easily accessible, as well as the community and managers in this case the Tourism Office and BUMDES (Village-Owned Enterprises) which support the Development of Tourism Objects. (2) Efforts can be made to develop tourist objects based on a SWOT analysis, namely, for the government by improving facilities and infrastructure such as improving the conditions of entry roads, repairing toilets, adding facilities such as gazebos and seats as well as souvenir kiosks and repairing parking lots. In addition, making programs such as tourism promotion and designing tourism object development that are more detailed and clear. In terms of the community, namely by maintaining the quality and sustainability and naturalness of tourism objects and being friendly to tourists